2009
DOI: 10.3802/jgo.2009.20.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation in patients with early epithelial ovarian cancer

Abstract: Objective: To assess the role of fertility preservation in the treatment of patients with early epithelial ovarian cancer (EOC). Methods: We retrospectively analyzed the medical records of 21 patients with early EOC from January 1995 to December 2006. All eligible patients with a strong desire to preserve fertility were younger than 35 years and underwent fertility-sparing surgery with or without adjuvant chemotherapy. Results: Twenty-one eligible patients with a median age of 26.7 years (range, 20 to 33 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 17 publications
(12 reference statements)
1
28
0
Order By: Relevance
“…The tumor type distribution showed a substantial variation between studies (e.g. mucinous tumors ranging from 36.2% [28] to 76.2% [25]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tumor type distribution showed a substantial variation between studies (e.g. mucinous tumors ranging from 36.2% [28] to 76.2% [25]).…”
Section: Resultsmentioning
confidence: 99%
“…The administration of adjuvant chemotherapy varied between studies: Whereas in some studies all patients received chemotherapy with a regimen depending on the stage/grade and/or completeness of surgical staging [19,29], other authors reported chemotherapy in a varying percentage of patients depending on the tumor stage and biological criteria [13,16,22,23,25,26] or without clear criteria of indication [12,20,21,24,31,32] (table 1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety of fertility-sparing surgery in women with stage IC and grade 3 EOC has not been determined, although the results of several recent series have suggested that fertility-sparing surgery is safe in patients with stage IC grade 1-2 EOC, regardless of the type of stage 1C (positive peritoneal cytology, capsule invasion or tumor rupture) [19,20,23,25,28,29,32,33,34,35,36,37,38,39]. Patients with preoperative or intraoperative tumor rupture, surface excrescences, or malignant cells in ascitic fluid or peritoneal washings are classified as having stage IC disease.…”
Section: Text Of Reviewmentioning
confidence: 99%
“…In most studies, including this review, fertility-sparing surgery has been defined as the preservation of ovarian tissue in one or both adnexa and the uterus in women of reproductive age [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39] (table 1). To date, 918 patients with EOC who underwent fertility-sparing surgery have been captured in the literature.…”
Section: Text Of Reviewmentioning
confidence: 99%